PENGARUH PEOPLE DAN PROCESS TERHADAP LOYALTY YANG DIMEDIASI OLEH SATISFACTION PADA NASABAH PT BANK SYARIAH INDONESIA (BSI) CABANG DARUSSALAM-BANDA ACEH - Rona Susanti; Ahmad Nizam (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to measure the influence of people and process on loyalty mediated by satisfaction with PT. Bank Syariah Indonesia (BSI) Darussalam Branch Banda Aceh. The sample used in this study was the customer of the Indonesian Sharia Bank (BSI) Darussalam branch, amounting to 200 respondents. The data collection equipment used in this study was a questionnaire. The sampling technique used is purposive sampling. Structural equation modeling (SEM) was used as an analytical method to determine the effect between the variables involved. Based on SEM analysis identified that people have a positive effect on loyalty, process has a positive effect on loyalty, people have a positive effect on satisfaction, process has a positive effect on satisfaction, satisfaction has a positive effect on loyalty, satisfaction has a positive effect on loyalty, satisfaction mediates the influence of society on loyalty, and satisfaction process mediates the effect on loyalty.